Waldwissen Professionalisierung der Forstwissenschaft in Hann. Münden 1868-1972 - Steinsiek, Peter-Michael (Universitätsverlag Göttingen, 2023)
How can one imagine the emergence and development of a scientific discipline? Can it be compared to the growth of a tree in the forest, which at first grows from tender beginnings and under the umbrella of the big ones, gaining strength and girth in order to finally be able to assert its place and habitat, dependent on the sustained supply of vital substances and symbioses, on an environment appropriate to it, yet always endangered by competition and unforeseeable misfortunes? It is certain that the "tree of knowledge", the science of the forest and its relations to the natural and social environment, had already left the juvenile stage behind it when a second Prussian forestry school opened its doors as a school of sustainability in Hann. Münden in 1868. The focus was on training forestry administrators for service in northern, central and western Germany. However, even in the early phase of the Forestry Academy, the teachers were called to Münden as scientists, primarily to clarify day-to-day questions of forest management in coordination with practice.Using the example of the Münden Forestry Academy, from which the Göttingen Faculty of Forest Sciences and Forest Ecology was later to emerge, this volume provides a look at the development of the professional foundations and the formation of forestry science. He describes the content of research in its dependence on factors from practice, science, politics and society. Also of interest is the question of what influence the fear of closure of the institution had on research strategy programmes during the period under study and how the unity of the faculty was preserved. Translated with www.DeepL.com/Translator (free version)